Evaluation of electrospun poly(ε-caprolactone)/gelatin nanofiber mats containing clove essential oil for antibacterial wound dressing - Ünalan, Irem; Endlein, Stefan J.; Slavik, Benedikt; Büttner, Andrea; Goldmann, Wolfgang; Detsch, Rainer; Boccaccini, Aldo R. (Pharmaceutics, 2019)
The objective of this study was to produce antibacterial poly(ε-caprolactone) (PCL)-gelatin (GEL) electrospun nanofiber mats containing clove essential oil (CLV) using glacial acetic acid (GAA) as a “benign” (non-toxic) solvent. The addition of CLV increased the fiber diameter from 241 ± 96 to 305 ± 82 nm. Aside from this, the wettability of PCL-GEL nanofiber mats was increased by the addition of CLV. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the presence of CLV, and the actual content of CLV was determined by gas chromatography–mass spectrometry (GC-MS). Our investigations showed that CLV-loaded PCL-GEL nanofiber mats did not have cytotoxic effects on normal human dermal fibroblast (NHDF) cells. On the other hand, the fibers exhibited antibacterial activity against Staphylococcus aureus and Escherichia coli. Consequently, PCL-GEL/CLV nanofiber mats are potential candidates for antibiotic-free wound healing applications.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Antibacterial; Biocompatibility; Clove essential oil; Electrospinning; Gelatin; PCL